An Analysis upon Various Contribution and Perspectives of Lok Adalat as an Effective and Legal Justice System: Promoting Justice and Equality through Lok Adalat (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Lok Adalat has been very successful in settlement of motor accident claim cases, matrimonial/family disputes, labor disputes, and disputes relating to public services such as telephone, electricity, and bank recovery cases as so on. The advent of Legal Services Authorities Act, 1987 gave a statutory status to Lok Adalatas, It is an Act to constitute Legal Services Authorities to provide free and competent legal services to the weaker sections of the society to ensure that opportunities for securing justice are not denied to any citizen by reason of economic or other disabilities, and to organize Lok Adalatas to secure that the operation of the legal system promotes justice on a basis of equal opportunity. Even before the enforcement of the Act, the concept of Lok Adalat had been getting wide acceptance as People's Courts as the very name signifies. Settlement of disputes at the hands of Panchayat Heads or tribal heads was in vogue since ancient times. When statutory recognition had been given to Lok Adalat, it was specifically provided that the award passed by the Lok Adalat formulating the terms of compromise will have the force of decree of a court which can be executed as a civil court decree.The forum of Lok Adalat is an integral part of the Indian Constitutional scheme enshrined in Preamble, Part III and Part IV of the Constitution. The system fulfills the requirement of justice to socially and economically backward people by resolving their disputes free of cost. Lok Adalats save the expensive civil proceeding, it saves the time which is often taken in obtaining justice or bare relief; and parties go out with faces beaming with smile and hand in hand.